Femoral rotational asymmetry is a common anatomical variant. Issue 4 (8th February 2018) - Newman, Christopher R.; Walter, William L.; Talbot, Simon
Abstract : The sulcus line (SL) is a three‐dimensional landmark that corrects for individual variation in the coronal alignment of the trochlear groove in contrast to the traditional Whiteside's line (WL). Femoral rotational asymmetry (FRA) is an anatomical variation in which the posterior condyles and trochlear groove are not perpendicular to each other. This study aims to measure the SL and assess its reliability relative to WL, in addition to measuring and classifying the FRA. A retrospective analysis of a series of 191 CT scans of nonarthritic knees was performed. Measurements were taken of rotational landmarks in three‐dimensional reconstructions. The variability and outlier rate of SL was less than WL ( P  < 0.05), however, it was also greater than the posterior condylar line (PC) ( P  < 0.05). Averaging the PC + 3° and the SL did not change the rate of femoral malrotation relative to the surgical epicondylar axis (SEA) ( P  > 0.05), however it decreased the rate of change of the rotational alignment of the trochlear groove between the native knee and the prosthetic knee from 31% to 5% ( P  < 0.05). FRA was classified and was >5° in 56/191 (29%) of cases. The SL technique is more accurate than WL for determining the rotational alignment of the trochlear groove. Nonarthritic femora have a high rate of rotational asymmetry. Identifying and classifying FRA in individual cases allows the femoral component to be inserted in a position which gives the best possible match to both the native posterior condyles and trochlear groove. Clin. Anat. 31:551–559, 2018. © 2018 Wiley Periodicals, Inc.